If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -22) = -25 Reorder the terms: (-22 + 4x) = -25 Remove parenthesis around (-22 + 4x) -22 + 4x = -25 Solving -22 + 4x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 4x = -25 + 22 Combine like terms: -22 + 22 = 0 0 + 4x = -25 + 22 4x = -25 + 22 Combine like terms: -25 + 22 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75
| 28+3x=76 | | -19=11m-8m | | -12w+12+8w=9+8w-12 | | 3x+6=2x-1+7 | | (7+3t)/4=-(t/8) | | -4(21-7y)=56 | | x-8=3.14 | | 6x+4=x+3 | | -25-2x=87 | | n/6-3=8 | | 3+x/3=6 | | 8+y1/6=0 | | 9/10+z=1/2 | | 4x+81+1/2=360 | | .5x+1.5y+3z=20 | | -2n-16=3n-6 | | 180-(60-2x)=180 | | 12/5w=108/5 | | x/9+2=0 | | 4a+b=4a | | 14+2x-4x=20 | | -(2/5)c=30 | | 4(2x+2)+61=11x+6-3x+63 | | n/4-4=-5 | | 1+4r+1+8r= | | 1/8+r=0 | | 4m-7=4m+17 | | 1+8z+z^2=0 | | 16.5+3t=0.9-t/-5 | | 4y-(y-3)=-18 | | -3(b+12)=-9 | | 3-10x=x+4 |